Giant Splenic Artery Pseudoaneurysm Mimicking Pancreatic Mass - R. A. Mammadov,; S. S. Mammadova,; F. A. Gahramanova,; Sh. A. Mammadova,; A. B. Hasanov,; N. Yu. Bayramov, (International Journal of Innovative Research in Medical Science, 2021)
Splenic artery aneurysm (SAA) is a rare condition in abdominal surgery and the third most abdominal aneurysm after aortic and iliac artery aneurysms. Open surgery during the giant SAA is still the gold standard of treatment. Here we present the case of the giant SAA in a 68-year-old man. He had a pancreatic mass and iron deficiency anemia. The diagnosis was confirmed by ultrasound and CT angiography and showed a pancreatic mass and expansion of the splenic artery more than 3.5 cm. The size of the aneurysm and the clinical picture of the patient were indications for open surgery. The patient was treated by resection of the spleen and distal pancreatectomy with the aneurysmal part of the splenic artery. As far as we know, open surgery is still the best treatment choice, despite some advances in endovascular methods.